(untitled) (American Journal of Development Studies, 2023)
Women are significantly affected by COVID-19 pandemic. The sexist and discriminatory practices and roles have even burdened them. With the challenges and problems that they encountered; this paper analyzed how the lives of young women have been affected during the pandemic. It also explores on their recovery and resilience strategies by highlighting their experiences and work activities to help sustain the basic needs of their families. Using gender lens to studying women’s lives and experiences, a qualitative design of face-to face, in-depth interviews was employed. Interpretative phenomenological analysis was used to analyze the data. The study group consisted of young women aged 24-29 (students and non-students) and were previously part of a non-skilled work sector who lost their jobs during the pandemic. Findings were presented according to time frame; their lived experiences before and during the Covid-19 pandemic. Three main themes were drawn from the findings: the trend of social media, social capital, and the personality of women. The result indicated that COVID-19 pandemic had triggered the preconceived notion of gender roles. Productivity and sustainability have even dwindled. Although challenged by work restrictions, young women have shown different kinds of resilience and coping strategies to provide the needs of the family especially of their children. Women’s strategies and mechanisms have debunked the stereotypical knowledge and preconceived notions about women. Unlike the notion that men work for the family, women are in fact active and responsible agents of economic development.